Water : local-level management - Brooks, David B., 1934- (In focus (International Development Research Centre (Canada)), 2002)
"Today, more than 1 billion people lack access to safe drinking water. Within the next 25 years, fully one-third of the world's population will experience severe water scarcity. It is clear that disparities in the availability and supply of fresh water are truly a matter of life and death, and constitute one of the great governance imperatives of our time." "This publication summarizes the results of three decades of IDRC-supported research on water supply. It demonstrates that some of the most powerful responses to water scarcities have been mounted at the community or local level - in households, farmers' fields, villages, and city neighbourhoods. With a focus on research findings, and failures, this book presents solidly grounded propositions for decision-makers and for researchers. It goes on to form a series of clear and pointed recommendations for policy design and future research efforts, and concludes with an eye to the future of water supply and a presentation of some of the key resources in the field."--Jacket